University Social Responsibility during the COVID-19 Pandemic: Universities’ Case in the BRICS Countries - Rababah, Abedalqader; Nikitina, Natalya I.; Grebennikova, Veronica M.; Gardanova, Zhanna R.; Zekiy, Angelina O.; Ponkratov, Vadim V.; Bashkirova, Nadezhda N.; Kuznetsov, Nikolay V.; Volkova, Tatyana I.; Vasiljeva, Marina V.; Ivleva, Marina I.; Elyakova, Izabella D. (Sustainability, 2021)
University social responsibility (USR) is an important assessment criterion of the QS Stars. In the context of the COVID-19 pandemic, the social orientation of universities as intellectual leaders in the development of society gains particular importance. The research purpose is to analyze the impact of the COVID-19 pandemic on the university activity directions in the framework of strategies (USR). An empirical assessment of the level and complementary factors of USR in the BRICS countries (Brazil, Russia, India, China, and South Africa) was conducted, using the method of integral and expert assessment. Grounded on scoring according to the principal component analysis, the structure of the factors of the USR development in the BRICS countries was determined. Multifactor regression modeling allowed substantiating the priority of factors stimulating the development of USR in the BRICS countries in modern conditions and arguing the main barriers to introducing the concept of social responsibility into university activities and expanding the stakeholders’ circle in it. The research results showed that the university management creativity, effective communication with the public and stakeholders, the quality of the educational process and the development of scientific activities stimulate USR development in the BRICS countries and should be used as the basis for the strategic planning of activities in the context of the continuing COVID-19 pandemic. Conceptual trends in the USR development can be useful for universities in the studied countries when adapting strategic development plans regarding the social needs of modern society.
Number: 13 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Libre accès; Responsabilité sociale; Rôle des universités; Université

University Social Responsibility during the COVID-19 Pandemic: Universities’ Case in the BRICS Countries - Rababah, Abedalqader; Nikitina, Natalya I.; Grebennikova, Veronica M.; Gardanova, Zhanna R.; Zekiy, Angelina O.; Ponkratov, Vadim V.; Bashkirova, Nadezhda N.; Kuznetsov, Nikolay V.; Volkova, Tatyana I.; Vasiljeva, Marina V.; Ivleva, Marina I.; Elyakova, Izabella D. (Sustainability, 2021)
University social responsibility (USR) is an important assessment criterion of the QS Stars. In the context of the COVID-19 pandemic, the social orientation of universities as intellectual leaders in the development of society gains particular importance. The research purpose is to analyze the impact of the COVID-19 pandemic on the university activity directions in the framework of strategies (USR). An empirical assessment of the level and complementary factors of USR in the BRICS countries (Brazil, Russia, India, China, and South Africa) was conducted, using the method of integral and expert assessment. Grounded on scoring according to the principal component analysis, the structure of the factors of the USR development in the BRICS countries was determined. Multifactor regression modeling allowed substantiating the priority of factors stimulating the development of USR in the BRICS countries in modern conditions and arguing the main barriers to introducing the concept of social responsibility into university activities and expanding the stakeholders’ circle in it. The research results showed that the university management creativity, effective communication with the public and stakeholders, the quality of the educational process and the development of scientific activities stimulate USR development in the BRICS countries and should be used as the basis for the strategic planning of activities in the context of the continuing COVID-19 pandemic. Conceptual trends in the USR development can be useful for universities in the studied countries when adapting strategic development plans regarding the social needs of modern society.
Number: 13 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Libre accès; Responsabilité sociale; Rôle des universités; Université